Persepsi Estetika Masyarakat Indonesia Terhadap Karya NFT Populer - Ruth Ardianti; Ely Andra Widharta (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
This is a descriptive study that examines the Indonesian people's comprehension of NFT and the popularity of NFT (Non-Fungible Token) using qualitative and quantitative data analysis. Since the explosion of Ghozali Everyday's NFT works in Indonesia in 2021, it has been an attraction for the Indonesian people to learn "What is NFT" and "How does NFT work?". The objectives of this study are as follows: (1) to establish the features of popular NFT goods among users; and (2) to assess Indonesian people's aesthetic opinion of the popularity of NFT products. The findings revealed that; first, the aesthetic analysis of The most popular works in the NFT Opensea marketplace have various features, including (a) character selection, (b) picture object capture, (c) style selection, and (d) usage value. It is believed that this research would aid in understanding the situation of the Indonesian people about societal phenomena, particularly NFT (non-fungible tokens), so that they may be utilized as references for the academic community, users, or art watchers with an interest in NFT products.